Estimating the cost of delivering direct nutrition interventions at scale: National and subnational level insights from India - Menon, Purnima; McDonald, C. M.; Chakrabarti, Suman (International Food Policy Research Institute, 2015)
Undernutrition imposes a staggering cost worldwide in terms of lives lost, forgone productivity, healthcare spending, and reduced lifetime earnings (Horton et al. 2010). In India, nutrition policies recognize the multifaceted nature of interventions necessary to accelerate progress in nutrition. These interventions include a set of broadly agreed upon nutrition-specific interventions such as iron and folic acid supplementation during pregnancy, breastfeeding promotion, complementary feeding education, vitamin-A supplementation in early childhood, food supplementation (Avula et al. 2013) that are to be delivered at scale to improve maternal and child nutrition. Two national programs in India—Integrated Child Development Services (ICDS) and National Rural Health Mission (NRHM)—together are designed to cover all of these nutrition-specific interventions (Avula et al. 2013).